Keterampilan Metakognitif Siswa Kelas XI SMA NW Mataram Pada Matapelajaran Biologi - R. Didi Kuswara; L. Fauzi Haryadi; L. Ependi; Nadzar Abd. Basith; Eka Marta Rahayu (Otus Education: Jurnal Biologi dan Pendidikan Biologi, 2023)
Metacognitive skills are one of the skills that can influence people's lives and ways of thinking regarding self-management. This research aims to describe students' metacognitive abilities, especially in class XI biology subjects at Nahdlatul Wathan Mataram High School, which consists of classes XI MIA and XI IIS. Data collection was carried out using a questionnaire by looking at metacognitive skills from three aspects, namely planning, monitoring and evaluation. Based on these three aspects, it shows that class XI students at NW Mataram High School do not have low category metacognitive skills or are not well developed. Based on the results of the questionnaire scoring, it was found that on average students answered sometimes or never. This shows that their awareness of planning, monitoring and evaluating their learning process is very low and of course this also has an impact on learning outcomes. This is what requires teachers to be able to implement learning that can develop students' metacognitive skills, so that learning outcomes will increase.